(3JGL GdJQGLe aj WHbGJ GdMfajIs - (3bGSe Hf bWdhHZG, Rjf GdOjf, CHh GdYOd GdShOhfj GdLeGdj,J (B879 (3g` s ((3YHO Gddg Hf Ydi Hf CHj GdMSf Hf Ydi GdHOjhi s)
(3ChdgG (B:s
(3deG hbaJ Ydi JPcQI TjNfG GdebQjRiGdN s
(3BNQgG (B:s
(3JeJ HMeO Gddg hYhfg hMSf Jhajbg s
(3gh eNJUQ ai JQGLe YdeGA GdMfajI LeYg ef JPcQI TjNg Jbi GdOjf GdebQjRis
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B180 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B111s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B82 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B55 s
Keywords: (3GdJGQjNs